IL-7 receptor influences anti-TNF responsiveness and T cell gut homing in inflammatory bowel disease - Lyssia Belarif; Richard Danger; Laetitia Kermarrec; Véronique Nerrière-Daguin; Sabrina Pengam; Tony Durand; Caroline Mary; Elise Kerdreux; Vanessa Gauttier; Aneta Kucik; Virginie Thepenier; Jerome C. Martin; et al. (The Journal of Clinical Investigation, 2019)
It remains unknown what causes inflammatory bowel disease (IBD), including signaling networks perpetuating chronic gastrointestinal inflammation in Crohn’s disease (CD) and ulcerative colitis (UC), in humans. According to an analysis of up to 500 patients with IBD and 100 controls, we report that key transcripts of the IL-7 receptor (IL-7R) pathway are accumulated in inflamed colon tissues of severe CD and UC patients not responding to either immunosuppressive/corticosteroid, anti-TNF, or anti-α4β7 therapies. High expression of both IL7R and IL-7R signaling signature in the colon before treatment is strongly associated with nonresponsiveness to anti-TNF therapy. While in mice IL-7 is known to play a role in systemic inflammation, we found that in humans IL-7 also controlled α4β7 integrin expression and imprinted gut-homing specificity on T cells. IL-7R blockade reduced human T cell homing to the gut and colonic inflammation in vivo in humanized mouse models, and altered effector T cells in colon explants from UC patients grown ex vivo. Our findings show that failure of current treatments for CD and UC is strongly associated with an overexpressed IL-7R signaling pathway and point to IL-7R as a relevant therapeutic target and potential biomarker to fill an unmet need in clinical IBD detection and treatment.